(untitled) (Journal of the Bangladesh Agricultural University, 2020)
An experiment was conducted with wet rice straw (WRS) treated with poultry droppings (PD) and molasses to increase the nutritional and preservation quality by ensiling. Five different combination was prepared as T0 (100% WRS), T1 (5% Molasses + 95% WRS), T2 (5% PD+ 5% Molasses+ 90% WRS), T3 (10% PD + 5% Molasses+ 85% WRS) and T4 (15% PD+ 5% Molasses+ 80% WRS). The mixed ingredients were preserved in plastic containers under airtight condition at room temperature. Physical quality, chemical composition, in-vitro organic matter digestibility (IVOMD) and Metabolizable Energy (ME) content at 0, 30, 45, 60 and 90 days were measured and calculated. The physical quality (color, smell, and hardness) of straw improved in PD added treatments till 90 days of ensiling except in T4 where some pungent smell was found after 60 days. The pH value was decreased (P<0.05) with the increasing of droppings and ensiling time as expected. The significantly (P<0.05) highest average crude protein (CP) and lowest average ether extract (EE) and crude fiber (CF) content was found in T4 indicating greater fermentation rate with greater proportion of poultry droppings. Dry matter, EE and CF content were found highest in T0 which indicate poor fermentation. The CP increased (P<0.05) and DM, EE and CF decreased (P<0.05) with the increasing of ensiling time from 0 to 90 days. The ash content decreased (P<0.05) significantly with the increase of PD and ensiling time. The Organic Matter Digestibility (OMD) and Metabolizable Energy (ME) content increased (P<0.05) with the PD level. The highest OMD and ME content were found to be 56.46% and 6.98 MJ/Kg DM in T4 and the lowest OMD and ME content were found to be 53.31% and 4.88 MJ/Kg DM in T0, respectively. Considering all the physical and chemical properties among all the treatments T3 (10% PD + 5% Molasses+ 85% WRS) can be marked acceptable for preparing ensilage as the dark chocolate color, pungent odor and presence of fungus in later stage of T4 may result in rejection by cattle. Proper ensiling of WRS with PD will not only reduce waste disposal hazards and environment pollution problem but also provide inexpensive feed components for ruminants. J Bangladesh Agril Univ 18(3): 651–659, 2020 https://doi.org/10.5455/JBAU.103080